Method for preparing anti-corrosion composite coating of PEM metal bipolar plate and composite coating

Through multi-arc ion coating and magnetic filtration technology, non-precious metal composite coatings are prepared, which solves the problem of insufficient corrosion resistance of the coating in PEM water electrolytic cells, and realizes a high-performance and low-cost coating process, which is suitable for industrial production.

CN119121277AInactive Publication Date: 2024-12-13SHANGHAI ELECTRICGROUP CORP

Patent Information

Application Number
CN202411274632.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PEM water electrolytic cell metal bipolar plate surface coating has problems of insufficient comprehensive performance in terms of corrosion resistance and electrical conductivity, especially the cost of precious metal coatings is high and difficult to meet the needs of industrial production.

Method used

Multi-arc ion coating technology combined with magnetic filtration technology is used to prepare composite coatings of non-precious metal substrates and buffer layers, reduce the use of precious metals, improve the corrosion resistance and conductivity of the coating, and form an efficient and low-cost coating process.

Benefits of technology

It effectively reduces the use of precious metal coatings, improves the corrosion resistance and conductivity of the coating, and realizes a high-performance and low-cost coating solution. It is suitable for mass production and meets the industrialization needs of PEM electrolytic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121277A_ABST
    Figure CN119121277A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an anti-corrosion composite coating of a PEM metal bipolar plate and a composite coating, the method for preparing the anti-corrosion composite coating of the PEM metal bipolar plate comprises the following steps: step S1, polishing the surface of a metal substrate, then cleaning by adopting an automatic cleaning assembly line, a rust remover or a hydrochloric acid solution, and then cleaning by adopting an automatic cleaning assembly line; drying at constant temperature for later use; the method has the beneficial effects that aiming at the limitation of the precious metal coating of the existing PEM electrolytic cell on industrial production, a large number of comparative research experiments are performed for reducing the use of the precious metal coating, the non-precious metal coating is used, the use of the precious metal coating is reduced, and the research in the aspect of an efficient coating production process is performed; and a set of engineering coating technical scheme with excellent performance and low cost is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PEM metal bipolar plate anti-corrosion composite coatings, and in particular to a method for preparing a PEM metal bipolar plate anti-corrosion composite coating and the composite coating. Background Art

[0002] As an attractive alternative energy carrier, hydrogen shows great potential in alleviating the world's over-dependence on non-renewable resources due to its high energy density (140MJ kg-1) and eco-friendly characteristics; hydrogen is considered to be an ideal energy carrier for the future energy society with its advantages of zero emissions and high energy density.

[0003] Renewable energy electrolysis of water to produce hydrogen is an efficient, clean and pollution-free production process with high purity of hydrogen. It can not only significantly reduce the cost of green hydrogen and make it industrially economical, but also effectively solve the problem of renewable energy "depending on the weather". Compared with the low purity and high content of carbon-containing species caused by catalytic reforming of fossil fuels, water electrolysis can produce high-quality hydrogen (≈100%).

[0004] Proton exchange membrane electrolyzer (PEM) technology has the advantages of compact structure, fast response speed, high current density, strong adaptability to fluctuations, and high purity of hydrogen production, which enables it to be better combined with renewable energy. Therefore, PEM water electrolysis hydrogen production technology is an important technical path for renewable energy hydrogen production in the future. Bipolar plates are one of the key components of PEM water electrolyzers. Metal bipolar plates are currently the most commonly used bipolar plate materials. However, the working environment of the anode of PEM water electrolyzers is harsh, generally acidic, humid, and warm. The corrosion products of metal bipolar plates will contaminate the catalyst and form a passivation layer on the surface of the metal plate, resulting in an increase in the contact resistance between the bipolar plate and the diffusion layer. Metals are easily corroded, resulting in the leaching of metal ions, which in turn contaminate the PEM water electrolyzer.

[0005] The current solution is to use high-purity materials as the bipolar plate substrate structure and apply anti-corrosion coating on the surface of the bipolar plate to reduce the problem of anodic oxidation. However, in general, the better the conductivity of the coating, the worse the corrosion resistance, which is the biggest bottleneck restricting the development of metal bipolar plate surface coating.

[0006] At present, the most commonly used coatings for the most basic bipolar plates of PEM water electrolyzers are Ti-Ag films, (Ti, Zr) N, ruthenium oxide, platinum and gold, etc. It can be seen that precious metal coatings are the mainstream and the dosage is very large. So far, a large number of studies on corrosion-resistant coatings on the surfaces of metal bipolar plates have been proposed. According to the classification of coating materials, they can be divided into: metal coatings, which include inert metal coatings, transition metal nitride coatings, metal oxide coatings and transition metal carbide coatings, as well as carbon-based coatings and conductive polymer coatings. Among them, transition metal nitride coatings and carbon-based coatings are more prominent in conductivity and corrosion resistance, and are more likely to meet the requirements of DOE 2025. Most conductive polymer coatings cannot meet the requirements of DOE 2025. Obviously, metal nitride coatings and carbon-based coatings are currently the best choices for protective coatings for metal bipolar plates. Summary of the invention

[0007] In order to overcome the problem of insufficient comprehensive performance of the current protective coating when applied to the surface of metal bipolar plates in the prior art, the present invention provides a method for preparing a corrosion-resistant composite coating for PEM metal bipolar plates and a composite coating.

[0008] The present invention discloses a method for preparing a PEM metal bipolar plate anti-corrosion composite coating, comprising the following steps:

[0009] Step S1: polishing the surface of the metal substrate, then cleaning it with an automatic cleaning line, a rust remover or a hydrochloric acid solution, and finally drying it at a constant temperature for standby use;

[0010] Step S2: firstly, the dried substrate is placed in a vacuum chamber, evacuated to a suitable back-end vacuum degree, and the substrate is bombarded with an ion source for 20 minutes to clean away large impurities on the surface of the substrate;

[0011] Step S3: introducing working gas and using a multi-arc source for coating;

[0012] Step S4: After the coating is completed, wait for the chamber to cool naturally before taking out the sample and storing it in a vacuum for subsequent testing.

[0013] On this basis, the process of the automatic cleaning line in step S1 includes degreasing, dewaxing, acid cleaning, alkaline cleaning and pure water ultrasound.

[0014] On this basis, the steps of cleaning the substrate with a rust remover or a hydrochloric acid solution in step S1 are as follows:

[0015] S11: Use a dust-free cloth to wipe off the dust generated by the surface cutting process;

[0016] S12: Use metal rust remover (WIN-267) as cleaning solution and perform ultrasonic cleaning for 10 minutes;

[0017] S13: Use alcohol as cleaning solution and perform ultrasonic cleaning for 5 minutes;

[0018] S14: Use pure water as the cleaning solution and perform ultrasonic cleaning for 5 minutes.

[0019] On this basis, the drying temperature in step S1 is set to 100° C. and the drying time is set to 20 minutes.

[0020] On this basis, the working gas in step S3 is nitrogen or argon.

[0021] On this basis, when the multi-arc source is used for coating in step S3, the ionization unit range is 0.2Pa-0.5Pa, the voltage range is 80V-800V, the coating time range is 60s-3600s, and the temperature range is 20°C-110°C. On this basis, magnetic filtration technology is added to the multi-arc ion plating technology in step S3, the time of magnetic filtration technology is 3600s, the gas pressure is 0.5Pa, the temperature range is 50°C-53°C, the voltage is 80V, and the argon gas flow rate is 180sccm.

[0022] A composite coating prepared by a method for preparing a PEM metal bipolar plate anti-corrosion composite coating comprises a buffer layer and a noble metal layer. The substrate, the buffer layer and the noble metal layer are arranged in sequence, and the buffer layer is a non-noble metal and its compound.

[0023] On this basis, the substrates are titanium, stainless steel and aluminum.

[0024] On this basis, the thickness of the protective film layer ranges from 0.48 μm to 0.87 μm.

[0025] On this basis, the material of the buffer layer is the same as that of the substrate.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) In view of the limitations of the existing PEM electrolyzer precious metal coating for industrial production, the present invention has conducted a large number of comparative research experiments on reducing the use of precious metal coatings, used non-precious metal coatings, reduced the use of precious metal coatings, and conducted research on efficient coating production processes, thus forming a set of engineering coating technology solutions with excellent performance and low cost.

[0028] (2) The present invention provides an optimized method for preparing metal bipolar plates for proton exchange membrane electrolysis cells. The addition of magnetic filtration technology during multi-arc ion plating can effectively reduce the number of pores on the surface of the sample after corrosion, improve the number of large particles in the deposited film layer, and prepare samples with better contact resistance and corrosion resistance.

[0029] (3) The composite coating method provided by the present invention adjusts the coating material, multi-layer composite coating, thickness, coating method, etc., combines the industrial development of PEM electrolytic cells, develops high-performance and low-cost coating solutions, and develops easy-to-operate corrosion-resistant composite coating preparation technology and mass production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The corrosion current density curves of Cr and Cr-CrN composite multilayer coatings under 2V constant potential polarization when using titanium substrate;

[0031] Figure 2 The corrosion current density curves of Zr and Zr-ZrN coatings under 2V constant potential polarization when using titanium substrate;

[0032] Figure 3 Polarization test results of TiN and Ti-TiN samples on titanium substrate at 2V (proton exchange membrane water electrolyzer);

[0033] Figure 4 is the potentiodynamic polarization curve of Cr-CrN multilayer coating on titanium substrate;

[0034] Figure 5 is the potentiodynamic polarization curve of Zr-ZrN multilayer coating and bare titanium substrate;

[0035] Figure 6 is the potential scanning curve of Ti-TiN coating;

[0036] Figure 7 It is the constant potential polarization curve of CrN coating on titanium substrate after hand-grinding excitation treatment and original sheet;

[0037] Figure 8 It is the constant potential polarization curve of TiN coating on titanium substrate after wire drawing and wire drawing and excitation treatment; Fig. 9 is the XRD pattern of the Ti-TiN multilayer coating sample;

[0038] Fig.10 The SEM surface morphology of the Ti-TiN coating on the titanium substrate before 2 hours of constant potential polarization test is shown;

[0039] Fig.11 The SEM surface morphology of the Ti-TiN coating Ti substrate after polarization;

[0040] Fig.12 SEM micrographs of TiN and Ti-TiN coatings on titanium substrate after 216 hours of constant potential testing. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] The present invention discloses a method for preparing a PEM metal bipolar plate anti-corrosion composite coating, comprising the following steps:

[0043] Step S1: polish the surface of the metal substrate, and then use an automatic cleaning line, a rust remover or a hydrochloric acid solution to clean it. The process of the automatic cleaning line includes degreasing, dewaxing, pickling, alkali cleaning and pure water ultrasound. The steps of cleaning the substrate with a rust remover or a hydrochloric acid solution are as follows: S11: wipe off the dust formed by the cutting process on the surface with a dust-free cloth; S12: use a metal rust remover (WIN-267) as a cleaning liquid, and ultrasonically clean for 10 minutes; S13: use alcohol as a cleaning liquid, and ultrasonically clean for 5 minutes; S14: use pure water as a cleaning liquid, and ultrasonically clean for 5 minutes; actually use one of the rust remover or the hydrochloric acid solution; finally, dry it at a constant temperature for use, the drying temperature is set to 100°C, and the time is 20 minutes;

[0044] Step S2: firstly, the dried substrate is placed in a vacuum chamber, evacuated to a suitable back-end vacuum degree, and the substrate is bombarded with an ion source for 20 minutes to clean away large impurities on the surface of the substrate;

[0045] Step S3: introducing working gas, which is nitrogen or argon, using a multi-arc source for coating, the ionization unit range is 0.2Pa~0.5Pa, the voltage range is 80V~800V, the coating time range is 60s~3600s, and the temperature range is 20℃~110℃; adding magnetic filtration technology to the coating with a multi-arc source, the time of the magnetic filtration technology is 3600s, the gas pressure is 0.5Pa, the temperature range is 50℃~53℃, the voltage is 80V, and the argon flow rate is 180sccm. The technology of using a multi-arc source for coating and magnetic filtration technology simultaneously, the coating thickness and bonding strength will affect the coating consistency, and then affect the contact resistance and corrosion current.

[0046] Step S4: After the coating is completed, wait for the chamber to cool naturally before taking out the sample and storing it in a vacuum for subsequent testing.

[0047] A composite coating prepared by a method for preparing a PEM metal bipolar plate anti-corrosion composite coating comprises a buffer layer and a noble metal layer. The substrate, the buffer layer and the noble metal layer are arranged in sequence. The buffer layer is a non-noble metal and its compound. The material of the buffer layer is the same as that of the substrate.

[0048] The substrate is titanium, stainless steel and aluminum. In this embodiment, the composition of the stainless steel is 0.07% carbon, 18.5% chromium, 2% manganese, 1% selenium, 0.045% phosphorus, 0.015% sulfur, 8% nickel, 0.1% nitrogen, and the rest is iron.

[0049] The thickness of the protective film layer ranges from 0.48μm to 0.87μm. As the thickness increases, the contact resistance first decreases and then remains flat.

[0050] The test method is as follows: The conductivity of the composite coating is tested using the Wang improved voltammetry method commonly used today, at 140N / cm 2 The contact resistance between the sample surface and the carbon paper (gas diffusion layer) was measured under compaction pressure. The effective test area was 7.06 cm 2 , apply 140N / cm 2 Pressure, record the reading after it stabilizes, and take the average value after measuring at least 3 to 5 times for each group.

[0051] The corrosion resistance of the coating was tested by electrochemical corrosion using Shanghai Chenhua CHI660E electrochemical workstation, including open circuit potential, dynamic potential polarization, constant potential polarization, etc., to evaluate the corrosion resistance of the coating. In the experiment, sulfuric acid solutions with pH = 0 and pH = 3 were used as corrosion media, and a traditional three-electrode system was used as the corrosion system, a 1cm×1cm platinum sheet was used as the counter electrode, a saturated calomel (SCE) solution was used as the reference electrode, and the working electrode was the prepared film sample. During the test, a constant temperature table / ceramic heating plate / oil bath was used to keep the solution at 60°C.

[0052] This study used constant potential polarization, dynamic potential scanning, and open circuit potential testing techniques to evaluate the corrosion resistance of the coating. Before the measurement, the potential was stabilized by an open circuit potential (OCP) test for one hour. Constant potential polarization is used to evaluate the long-term stability of the coating in a corrosive environment under actual working conditions. The corrosion time ranged from 2h to 200h, and the polarization potential was 0.8V, 2V, and 2.5V (vs. SCE). The change in current density at the corresponding potential was recorded.

[0053] Example

[0054] This embodiment provides a method for preparing a Ti, Zr, Cr, nitride system anti-corrosion film layer on a titanium, stainless steel, or aluminum metal substrate based on multi-arc ion plating technology and magnetron sputtering technology. The method comprises the following steps:

[0055] First, select a sample with a purity of 99.99% and a size of 50*50*3mm. 3Titanium is used as the substrate material. Before coating, it is subjected to surface treatments such as no treatment, manual polishing, water grinding, and brushing. Then it is degreased, dewaxed, pickled, alkaline washed, and subjected to pure water ultrasound. After cleaning, it is dried in a drying oven at a constant temperature of 100°C for at least 20 minutes and waits for coating.

[0056] Secondly, the dried substrate is placed in a vacuum chamber and evacuated to a back vacuum of 10^-3Pa to 10^-5Pa. The substrate is bombarded with an ion source for 20 minutes to clean off large particles of impurities on the surface of the substrate. Then, a working gas (N2 or Ar) is introduced and a multi-arc source is used for coating. After 1 to 60 minutes of coating, the substrate is naturally cooled to room temperature in an atmosphere of the working gas.

[0057] Multi-arc ion plating of metal and nitride monolayer film: Multi-arc ion plating system equipment is used to place the dried substrate into a vacuum chamber, and titanium, chromium, and zirconium targets with a purity of 99.99% are used for thin film deposition: the multi-arc ion plating working chamber is evacuated to a back vacuum of 8×10-3Pa; the substrate is bombarded with an ion source for 20 minutes to clean the large particle impurities on the substrate surface; the working gas is N2 and Ar, and a bias of -50V to -800V is applied during film coating to enhance the film bonding force. Six excitation power supplies are installed in the chamber to drive the arc spot on the surface of the target to move quickly during film coating, increase and change the transverse magnetic field strength, thereby reducing the large particles generated in multi-arc ion plating and making the deposited coating denser. Samples coated with Ti, Cr, Zr, TiN, ZrN, and CrN are obtained. After the coating is completed, the samples are taken out after the chamber is naturally cooled, and they are named Ti, Cr, Zr, TiN, ZrN, and CrN, and are stored in vacuum for subsequent testing. The preparation process parameters of the single-layer nitride sample are shown in Table 1:

[0058] Procedure Time(s) Air pressure (Pa) Temperature(℃) Voltage (V) Argon (sccm) Nitrogen (sccm) Vacuum 3600 5*10-3 20 - - - Cleaning target 60 2*10-1 20-45 800 150 0 Pre-sputtering 60 2*10-1 45-50 180 150 0 Magnetic Filtration 3600 5*10-1 50-53 80 180 0 Coating 3600 5*10-1 50-53 80 150 0

[0059] Table 1

[0060] Multi-arc ion plating deposition of metal-nitride multilayer film: The dried substrate is placed in a vacuum chamber, and titanium, chromium, and zirconium targets with a purity of 99.99% are used to perform the following cycle to complete the deposition of the film: samples coated with Ti, Cr, and Zr coatings are obtained by multi-arc ion plating (samples are named Ti, Cr, and Zr); N2 is then introduced to deposit the nitride coating, and each coating is plated for 5 minutes, and the metal and nitride are alternately plated for a total of 1 hour, that is, a total of 12 layers of composite film. After the coating is completed, the samples are taken out after the chamber is naturally cooled and named Ti-TiN, Cr-CrN, and Zr-ZrN. Vacuum storage for subsequent testing, the preparation process parameters of the multilayer nitride sample are shown in Table 2.

[0061] Procedure Time(s) Air pressure (Pa) Temperature(℃) Voltage (V) Argon (sccm) Nitrogen (sccm) Vacuum 3600 5*10-3 20 - - - Cleaning target 60 2*10-1 20-45 800 150 0 Pre-sputtering 60 2*10-1 45-50 180 150 0 Magnetic Filtration 3600 5*10-1 50-53 80 180 0 Coating (5*6) 1800 5*10-1 50-53 80 180 0 Coating (5*6) 1800 5*10-1 56-110 80 0 260

[0062] Table 2

[0063] Next, Wang's improved voltammetry method was used to test the contact resistance. The effective test area was 7.06 cm 2 , apply 140N / cm 2 Pressure, record after the reading is stable, and take the average value after measuring at least 3 to 5 times for each group. Shanghai Chenhua CHI660E electrochemical workstation was used for electrochemical corrosion test, including open circuit potential, dynamic potential polarization, constant potential polarization, etc., to evaluate the corrosion resistance of the coating. In the experiment, sulfuric acid solution with pH = 0 and pH = 3 was used as the corrosion medium, and the traditional three-electrode system was used as the corrosion system, 1cm × 1cm platinum sheet was used as the counter electrode, saturated calomel (SCE) solution was used as the reference electrode, and the working electrode was the prepared film sample. During the test, a constant temperature table / ceramic heating plate / oil bath was used to keep the solution at 60°C.

[0064] Finally, microstructure analysis was performed. Scanning electron microscope (SEM, Quanta250FEG): the scanning voltage was set to 0.1-30 kV, the beam current range was 1 pA-200 nA, the diameter was not less than 1 mm, the secondary electron image was 1.0 nm (15 kV), 1.5 nm (1 kV), the energy dispersive spectrometer (EDS) in the system was used to observe and analyze the microstructure and element distribution of the sample, the X-ray diffraction analyzer (XRD, BrukerD8Advanced) grazing incidence angle θ = 0.5°, 1°, 2°, 3°, the measurement range was set to 10-90° for analyzing the phase composition of the sample, and the X-ray photoelectron spectrometer (XPS) was used to analyze the composition and structure of the thin film sample.

[0065] refer to Figure 1 , is the corrosion current density of the coating under 2V constant potential polarization when using titanium substrate. Under the working conditions of proton exchange membrane water electrolyzer, the corrosion current density of Cr is 59.29μA / cm 2 , while the Cr-CrN composite multilayer coating has higher corrosion resistance, and the corrosion current density is 39.9μA / cm 2 The above coatings can all be used as alternative materials for corrosion-resistant coating materials for proton exchange membrane water electrolyzers. Compared with the single-layer C coating, the multilayer Cr-CrN coating has higher corrosion resistance because the interface between the multilayer films provides a physical barrier, changes the growth pattern of the crystal, and prevents the penetration of corrosive substances (acidic or other ions in the solution), thereby reducing the possibility of corrosion.

[0066] refer to Figure 2, is the corrosion current density of the coating under 2V constant potential polarization when using titanium substrate. The Zr-ZrN coating exhibits a more stable structure due to its multilayer interface and the passivation oxide layer on the titanium substrate. Under the working conditions of proton exchange membrane fuel cells, both Zr and Zr-ZrN coatings have lower corrosion current densities of 0.44μA / cm 2 and 0.23μA / cm 2 , once again proving that the Zr-ZrN coating exhibits more stable properties and better corrosion resistance due to the interface barrier on its multilayer structure; similarly, under the working conditions of the proton exchange membrane water electrolyzer, bubbles were observed on the surface of the sample, indicating corrosion occurred on the material, and the color of the solution turned dark, indicating oxidation on the surface of the material.

[0067] refer to Figure 3 , are the polarization test results of TiN and Ti-TiN samples on titanium substrate under 2V (proton exchange membrane water electrolyzer) environment, the corrosion current density of Ti-TiN under voltage, the polarization time is 2 hours, under the working conditions of proton exchange membrane water electrolyzer, some bubbles are generated on the sample surface, Ti, TiN and Ti-TiN coatings have good corrosion resistance, the corrosion current density is 22.76μA / cm 2 , 7μA / cm 2 and 5.77μA / cm 2 It can be clearly seen that the corrosion current density of the titanium substrate decreases continuously over time. The reason for this is that a 1.2-1.6 nm thick passive oxide film is immediately formed on the clean titanium surface exposed to air at room temperature.

[0068] refer to Figure 4 , is the potentiodynamic polarization curve of Cr-CrN multilayer coating on titanium substrate. Compared with the bare substrate, both have similar corrosion potential Ecorr on the anode side. It is generally believed that the more positive Ecorr tends to be, the stronger the corrosion resistance is. In addition, in the potentiodynamic test, as the scanning potential increases, the corresponding corrosion current density of Cr-CrN multilayer coating is 22.1μA / cm when it reaches 2V. 2 , and the corrosion current density of the bare titanium substrate is 41.2μA / cm 2 Compared with other materials, it has higher corrosion resistance.

[0069] refer to Figure 5 , is the potentiodynamic polarization curve of Zr-ZrN multilayer coating and bare titanium substrate. If the applied voltage is higher than the natural corrosion potential of the metal (also called open circuit potential), the corrosion process will be accelerated. It can be seen that the corrosion potential of the bare substrate is slightly higher, indicating that it is slightly less prone to corrosion.

[0070] refer to Figure 6, is the potential scanning curve of Ti-TiN coating, which is used to characterize the electrochemical corrosion performance of the substrate. The corrosion current density on the cathode side is 2.23μA / cm 2 , the anode side is 0.20μA / cm 2 For the uncoated titanium substrate, the cathode side is 7.22μA / cm 2 , the anode is 0.53μA / cm 2 , indicating that the corrosion resistance of the Ti substrate is improved by the multilayer coating. After the corrosion starts on the Ti substrate, TiO2 appears on the surface, which explains why the corrosion resistance increases over time when Ti is exposed to air. In the periodic table, Ti has an atomic number of 22 and has 4 electrons outside the nucleus, forming strong bonds with other elements. Therefore, it is difficult to break these bonds that make Ti more stable. Therefore, it was found that Ti, TiN and Ti-TiN coatings on titanium substrates have low current density.

[0071] refer to Figure 7 , is the constant potential polarization curve of CrN coating on titanium substrate after hand-polished excitation treatment and original film. Through the data of CrN plating on titanium substrate with different surface treatment methods, we can get that hand-polished mirror surface has better corrosion resistance than samples with other surface treatment methods. This is because the surface roughness of mirror polished excitation samples is low and there are fewer pores, which is conducive to improving the bonding ability between the film and the substrate, thereby improving the corrosion resistance of the sample.

[0072] refer to Figure 8 , is the constant potential polarization curve of TiN coating on titanium substrate after wire drawing and wire drawing and excitation treatment. The polarization potential is 2V, which meets the working conditions of proton exchange membrane water electrolyzer. After wire drawing and excitation treatment, the corrosion current density of Ti-TiN coating increases from 120.54μA / cm 2 Reduced to 9.37μA / cm 2 , which has been significantly reduced. Wire drawing and excitation processing can remove surface defects such as rough particles, scratches and contamination, which can serve as the starting point of corrosion "core" and accelerate the corrosion of the substrate in a corrosive environment. The smoother and more uniform surface reduces the possibility of localized corrosion and promotes the formation and stabilization of the protective oxide layer.

[0073] refer to Fig. 9 , is the XRD pattern of the Ti-TiN multilayer coating sample. It can be seen that these peaks indicate that Ti and TiN are deposited on the substrate with good crystallinity and the presence of a columnar growth structure.

[0074] refer to Fig.10, shows the SEM surface morphology of the Ti-TiN coating on the titanium substrate before 2 hours of constant potential polarization test. Due to the coating technology and material preparation, the coating efficiency is low or the surface performance is poor, and the surface of the Ti-TiN coating has microparticles and pores.

[0075] refer to Fig.11 , is the SEM surface morphology of the Ti-TiN coating Ti substrate after polarization, and the increase in the gap diameter can be clearly seen. However, the cavities still have not coalesced into large pits, which indicates that the corrosion has not yet penetrated deep, but the formation of these holes still increases the amount of corrosion of the material.

[0076] refer to Fig.12 , is the SEM micrograph of TiN and Ti-TiN coatings on titanium substrate after 216 hours of constant potential test. It can be seen that the narrow pores turned into shallow and wide pits, which led to the increase of corrosion current density and surface ICR value.

[0077] Based on the above data and test results, the present invention aims at the limitations of the existing PEM electrolytic cell precious metal coating for industrial production, conducts a large number of comparative research experiments to reduce the use of precious metal coatings, uses non-precious metal coatings, reduces the use of precious metal coatings, conducts research on efficient coating production processes, and forms a set of excellent performance and low-cost engineering coating technology solutions, which greatly reduces production costs; adding magnetic filtration technology during multi-arc ion plating can effectively reduce the number of pores on the surface of the sample after corrosion, improve the number of large particles in the deposited film layer, and prepare samples with better contact resistance and corrosion resistance;

[0078] This method develops a high-performance and low-cost coating solution by adjusting the coating material, multi-layer composite coating, thickness, and coating method, combined with the industrial development of PEM electrolyzers, and develops an easy-to-operate corrosion-resistant composite coating preparation technology and mass production process.

[0079] The above description shows and describes the preferred embodiments of the present invention. As mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a PEM metal bipolar plate anti-corrosion composite coating, characterized in that: The following steps are involved: Step S1: polishing the surface of the metal substrate, then cleaning it with an automatic cleaning line, a rust remover or a hydrochloric acid solution, and finally drying it at a constant temperature for standby use; Step S2: firstly, the dried substrate is placed in a vacuum chamber, evacuated to a suitable back-end vacuum degree, and the substrate is bombarded with an ion source for 20 minutes to clean away large impurities on the surface of the substrate; Step S3: introducing working gas and using a multi-arc source for coating; Step S4: After the coating is completed, wait for the chamber to cool naturally before taking out the sample and storing it in a vacuum for subsequent testing.

2. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: The process of the automatic cleaning line in step S1 includes degreasing, dewaxing, acid cleaning, alkaline cleaning and pure water ultrasound.

3. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: The steps of cleaning the substrate with a rust remover or a hydrochloric acid solution in step S1 are as follows: S11: Use a dust-free cloth to wipe off the dust generated by the surface cutting process; S12: Use metal rust remover (WIN-267) as cleaning solution and perform ultrasonic cleaning for 10 minutes; S13: Use alcohol as cleaning solution and perform ultrasonic cleaning for 5 minutes; S14: Use pure water as the cleaning solution and perform ultrasonic cleaning for 5 minutes.

4. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: In step S1, the drying temperature is set to 100° C. and the drying time is 20 minutes.

5. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: The working gas in step S3 is nitrogen or argon.

6. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: When the multi-arc source is used for coating in step S3, the ionization unit range is 0.2Pa-0.5Pa, the voltage range is 80V-800V, the coating time range is 60s-3600s, and the temperature range is 20°C-110°C.

7. The method for preparing the anti-corrosion composite coating of PEM metal bipolar plate according to claim 1, characterized in that: In the step S3, the magnetic filtration technology is added to the multi-arc ion plating technology. The time of the magnetic filtration technology is 3600s, the gas pressure is 0.5Pa, the temperature range is 50°C to 53°C, the voltage is 80V, and the argon gas flow rate is 180sccm.

8. A composite coating prepared by the method for preparing a PEM metal bipolar plate anti-corrosion composite coating according to any one of claims 1 to 7, characterized in that: It comprises a buffer layer and a noble metal layer. The substrate, the buffer layer and the noble metal layer are arranged in sequence. The buffer layer is a non-noble metal and its compound.

9. The composite coating according to claim 8, characterized in that: The substrates are titanium, stainless steel and aluminum.

10. The composite coating according to claim 8, characterized in that: The composite coating has a thickness ranging from 0.48 μm to 0.87 μm.

11. The composite coating according to claim 9, characterized in that: The material of the buffer layer is the same as that of the substrate.

Citation Information

Patent Citations

  • Surface modification method for thin titanium bipolar plate of proton exchange membrane fuel cell

    CN111244493A

  • Preparation process of ultralow-resistance corrosion-resistant coatings for metal bipolar plates of hydrogen fuel cells

    CN112111716A

  • Metal bipolar plate coating and preparation method thereof

    CN113584441A

  • Method for sputtering multiple coatings on surface of titanium substrate through direct current reaction

    CN114908318A

  • Preparation process of PEM fuel cell metal bipolar plate carbon-based composite coating

    CN115911436A

Cited By

  • Multi-element nitride corrosion-resistant coating on surface of seawater electrolysis bipolar plate and preparation method of multi-element nitride corrosion-resistant coating

    CN120796910A